The impact of leadership style and staff well-being on job satisfaction among academic staff in a Malaysian public university - Tengku Mohd Azzman, Malaysia; Syed Abdullah Idid, Syed Arabi; A. Manaf, Aini Maznina; Abdul Manan, Kamaruzzaman (2019)
Leadership style is an important factor in an organization. Previous studies have indicated that transformational leadership style can lead to increased organizational commitment, job satisfaction and organizational loyalty. However, the outcome of job satisfaction may also depend on the staff well-being, i.e. how far they are being challenged intellectually at the workplace, and the extent to which they are satisfied with their social interactions at the workplace. Thus, the main objective of this study is to identify factors that would predict job satisfaction among academic staff in a Malaysian public university. Specifically, it is predicted that transformational leadership style would mediate the relationship between intellectual and social well-being and job satisfaction. This study uses a cross-sectional survey to determine the relationship the relationship between transformational leadership style individual well-being and job satisfaction (N = 220). Respondents were instructed to provide responses on university leadership style, their well-being and job satisfaction at the public university through an online survey. Findings indicate that leadership style partially mediate the relationship between well-being and job satisfaction. The ramification of the findings on the impact of leadership style in the organizational context will be discussed.